Waste-Cooking-Oil Free Fatty Acid Reduction Using Deep Eutectic Solvent as Raw Material of Biodiesel - Mutiara Putri; Aida Syarif; Leila Kalsum (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
The purpose of this study was to extract the free fatty acid (FFA) of waste-cooking-oil through liquid-to-liquid extraction using choline chloride as a raw material for Deep Eutectic Solvent (DES) as a waste-cooking-oil purifier. Waste-cooking-oil is obtained from the waste of a fast food factory located in Sukarame, South Sumatera. Making a Dep Eutectic Solvent (DES) using compounds of ethylene glycol as Hydrogen Bond Donor mixed with a choline chloride Hydrogen Bond Acceptor with five molar ratios, a reaction temperature of 60 °C and a stirring speed of 150 rpm and 200 rpm for 90 minutes. The extraction molar ratio of waste-cooking-oil and DES with four ratios of molar ratios, extraction time of 2 hours at 60 °C and retention time of separation between DES and used cooking oil was 24 hours. The decrease in FFA of waste-cooking-oil was the highest at 83.87% in the DES 2. Its proves that DES is able to purify waste-cooking-oil by extraction methods to reduce FFA and adsorb other materials